Neuropsychological effects and attitudes in patients following electroconvulsive therapy - Miriam Feliu (Dove Medical Press, 2008)
Miriam Feliu1,2, Christopher L Edwards1,2,3, Shiv Sudhakar4, Camela McDougald1, Renee Raynor5, Stephanie Johnson6, Goldie Byrd7, Keith Whitfield8, Charles Jonassaint8, Heather Romero1, Lekisha Edwards1, Chante’ Wellington1, LaBarron K Hill9, James Sollers, III9, Patrick E Logue11Department of Psychiatry and Behavioral Sciences; 2Duke Pain and Palliative Care Center; 3Department of Medicine, Division of Hematology; 4Drexel University Medical School; 5Brain Tumor Center, Duke University Medical Center, Durham, NC, USA; 6Science Directorate, American Psychological Association; 7Department of Biology, North Carolina A&T State University; 8Department of Psychology, Duke University; 9Department of Psychology, The Ohio State UniversityAbstract: The current study examined the effects of electroconvulsive therapy (ECT) on neuropsychological test performance. Forty-six patients completed brief neuropsychological and psychological testing before and after receiving ECT for the treatment of recalcitrant and severe depression. Neuropsychological testing consisted of the Levin Selective Reminding Test (Levin) and Wechsler Memory Scale-Revised Edition (WMS-R). Self-report measures included the Beck Depression Inventory (BDI), the Short-Term Memory Questionnaire (STMQ), and several other measures of emotional functioning and patient attitudes toward ECT. The mean number of days between pre-ECT and post-ECT testing was 24. T-test revealed a significant decrease in subjective ratings of depression as rated by the BDI, t(45) = 9.82, P < 0.0001 (Pre-BDI = 27.9 ± 20.2; post-BDI = 13.5 ± 9.7). Objective ratings of memory appeared impaired following treatment, and patients’ self-report measures of memory confirmed this decline. More specifically, repeated measures MANOVA [Wilks Lambda F(11,30) = 4.3, p < 0.001] indicated significant decreases for measures of immediate recognition memory (p < 0.005), long-term storage (p < 0.05), delayed prose passage recall (p < 0.0001), percent retained of prose passages (p < 0.0001), and percent retained of visual designs (p < 0.0001). In addition, the number of double mentions on the Levin increased (p < 0.02). This study suggests that there may be a greater need to discuss the intermittent cognitive risks associated with ECT when obtaining informed consent prior to treatment. Further that self-reports of cognitive difficulties may persist even when depression has remitted. However, patients may not acknowledge or be aware of changes in their memory functioning, and post-ECT self-reports may not be reliable.Keywords: electroconvulsive therapy, neuropsychology, attitudes, memory